Pengaruh Pemberian Bubuk Daun Kelor Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri di Universitas ’Aisyiyah Surakarta - Shinta Selvianika; Rita Riyanti Kusumadewi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Adolescent girls are at a higher risk of decreased hemoglobin levels due to increased iron requirements during growth and menstruation. Low hemoglobin levels can lead to impaired concentration, reduced physical fitness, and limitations in daily activities. Moringa oleifera leaves contain iron, vitamin C, vitamin A, and protein, all of which play important roles in hemoglobin synthesis, making them a potential nutritional intervention to increase hemoglobin levels in adolescent girls. This study aimed to determine the effect of Moringa oleifera leaf powder supplementation on hemoglobin levels among female students at Universitas ’Aisyiyah Surakarta. This study employed a pre-experimental design using a one-group pretest–posttest approach. The sample consisted of 22 adolescent girls selected through simple random sampling. Hemoglobin levels were measured before and after the administration of Moringa oleifera leaf powder for seven days. Data were analyzed using the Paired Samples t-Test with a 95% confidence level. The mean hemoglobin level before the intervention was 11.945 g/dL, which increased to 13.545 g/dL after the intervention, with a mean increase of 1.600 g/dL. The results of the Paired Samples t-Test showed a p-value of